Analisis Pelaksanaan Praktikum Fisika di SMA Negeri Se-Kabupaten Maros - Anita M; Irma Sakti; Fitriani Kadir (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2022)
This study is a qualitative study that aims to analyze the implementation of physics practicum in public high schools throughout Maros Regency in 2022. The sample in this study was a public high school in Maros Regency which had an A accreditation, and the number of informants was 20 which were divided into 10 public high schools around the world. Maros Regency. The instruments used in this study were interview guide sheets and physics laboratory observation sheets. The data were analyzed using three stages, namely data reduction, data presentation, and conclusion drawing. Based on the results of observations of physics laboratories at public high schools throughout Maros Regency, the availability of facilities and infrastructure for the implementation of physics practicum can be classified as complete but there are still some that are still incomplete according to applicable standards, based on the results of interviews with physics teachers at public high schools throughout Maros Regency, the implementation of the physics practicum did not go well, because it was constrained by various things so that the practicum was not carried out optimally and in accordance with the curriculum. Based on the results of observations and interviews, it can be concluded that the implementation of physics practicum in Public High Schools throughout Maros Regency is carried out optimally and some is not optimal due to various obstacles.